DETERMINAN SISI PENAWARAN GREEN BONDS ASEAN - Wijaya, Richy; Dwi Hartini Rahayu; Salim Budiman (Media Ekonomi, 2024)
The explicit objective of this study is to analyze the factors influencing the supply side of Green Bonds in ASEAN countries. This research aims to examine how the characteristics of green bonds and the characteristics of issuing companies affect the amount of green bonds issued in ASEAN countries, particularly in Malaysia, Singapore, Thailand, and the Philippines during the period from 2018 to 2021. This study employs a quantitative research design with a linear regression analysis approach using the Ordinary Least Squares (OLS) method. This design was chosen to identify and measure the relationship between the independent variables (green bond characteristics and issuer company characteristics) and the dependent variable (the amount of green bonds issued). The independent variables in this study are Green Bond Characteristics, proxied by coupon rates and risk premiums. Additionally, the study includes the variable Issuer Company Characteristics, proxied by the debt ratio of the issuing company. The dependent variable in this study is the amount of green bonds issued. This research utilizes panel data that encompasses green bonds issued in four ASEAN countries (Malaysia, Singapore, Thailand, and the Philippines) from 2018-2021. This panel data allows for analysis that accounts for variability over time and across different companies or countries. The findings of this study indicate that there is a significant relationship between the characteristics of green bonds and the characteristics of issuing companies with the amount of green bonds issued in ASEAN countries. Specifically, it was found that green bond characteristics such as coupon rates and risk premiums significantly impact the amount of green bonds issued. Higher coupon rates and higher risk premiums tend to reduce the amount of green bonds issued. Additionally, the characteristics of the issuing companies, particularly the debt ratio, were also found to have a significant influence on the amount of green bonds issued. Companies with higher debt ratios tend to issue more green bonds. Overall, this study identifies key factors influencing the supply of green bonds in ASEAN and provides insights that can support the development of policies and strategies to strengthen the green bond market in the region